2020
DOI: 10.5888/pcd17.200047
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Social Media Use in the Field of Public Health Nutrition: Benefits, Scope, Limitations, and a Latin American Experience

Abstract: Social media platforms are low-cost tools that can be used to address issues in public health nutrition, especially in countries where health-related institutions experience economic limitations. We aimed to emphasize the benefits of using social media to promote health that have been documented to date. To show social media's positive impact on population health literacy, we briefly describe an inexpensive systematic communication strategy implemented in our research center through 2 social media platforms, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 35 publications
0
24
0
3
Order By: Relevance
“…Leveraging widely used social media platforms may be a promising approach to deliver DSME to underserved Chinese immigrants in a time and place that is convenient to them [ 24 , 25 ]. In a prior study, we demonstrated ownership of smart devices by a majority of Chinese immigrants with T2D, widespread use of the free social media app, “WeChat,” and a strong interest in a WeChat-based DSME [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging widely used social media platforms may be a promising approach to deliver DSME to underserved Chinese immigrants in a time and place that is convenient to them [ 24 , 25 ]. In a prior study, we demonstrated ownership of smart devices by a majority of Chinese immigrants with T2D, widespread use of the free social media app, “WeChat,” and a strong interest in a WeChat-based DSME [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Professional dermatology organizations and board-certified dermatologists have increased their public and professional engagement through social media. The use of social media has also gained recognition among the scientific community because its use is associated with higher article citation and increased accessibility to the general public [ 26 ]. In 2018, Patel et al revealed that the two most popular dermatology journals on social media were the Journal of the American Academy of Dermatology (JAAD) and JAMA Dermatology .…”
Section: Discussionmentioning
confidence: 99%
“…These compelling numbers are proof of the growing trend and usage of social media in the scientific community over the last few years. These platforms have become powerful instruments for health education that people from diverse age groups, locations, and economic statuses can use daily to learn and share knowledge [ 26 ]. Given this rise of dermatology content on social media, it is relevant to consider how social media is being used in regards to dermatological concerns and practices and how to best tackle them.…”
Section: Discussionmentioning
confidence: 99%
“…A noteworthy case is that of Mayo Clinic, engaged in the management of dozens of hospitals in the US and which through various social accounts on various platforms is constantly engaged in disease awareness and prevention. Also, on an international level, the National Cancer Institute [ 32 ] and the WHO [ 33 ] are also excellent examples of how you can communicate with social networks. Among the Italian institutions, AIFA is actively engaged in the use of social networks for communication to the public [ 34 ].…”
Section: Discussionmentioning
confidence: 99%